Do policy makers use academic research? reexamining the "two communities" theory of research utilization - Newman, Joshua; Head, Brian W.; Cherney, Adrian (2016)
Academics and policy makers in many Western countries are perceived as occupying separate communities, with distinct languages, values, and reward systems. However, data from a survey of more than 2,000 policy officials and 126 in-depth interviews with public servants in Australia suggest that the "two communities" conceptualization may be misleading and flawed. More realistically, there is a range of interaction between policy and academia, with some individuals valuing and using academic research more than others. Furthermore, this relationship is complicated by the internal division between the political and administrative components of the public policy process. - Reproduced.
Keywords: Research